2022
DOI: 10.3389/fpsyt.2022.913286
|View full text |Cite
|
Sign up to set email alerts
|

Catatonia Spectrum: Validation of a Questionnaire Investigating Catatonia Spectrum

Abstract: AimA growing body of literature has demonstrated the utility of a dimensional perspective on mental disorders. The current study aims to determine the psychometric properties of the Catatonia Spectrum (CS), a new questionnaire specifically tailored to assess the spectrum of catatonia, from full blown forms to subthreshold ones.Methods86 adults with at least three symptom criteria for catatonia according to the Diagnostic and Statistical Manual of Mental Disorders (DSM-5), 81 adults affected by borderline perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 22 publications
4
26
0
2
Order By: Relevance
“…In the validation study [ 34 ], the CS questionnaire demonstrated excellent internal consistency and test–retest reliability and strong convergent validity with alternative dimensional measures of catatonia, such as the Bush-Francis Catatonia Rating Scale and the Bush-Francis Catatonia Screening Instrument [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the validation study [ 34 ], the CS questionnaire demonstrated excellent internal consistency and test–retest reliability and strong convergent validity with alternative dimensional measures of catatonia, such as the Bush-Francis Catatonia Rating Scale and the Bush-Francis Catatonia Screening Instrument [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Catatonia Spectrum (CS) is a self-assessment questionnaire that investigates nuclear, subthreshold, atypical and partial manifestations of the CS, referred to across the lifespan, divided into domains, and explored with a set of questions. The CS consists of 74 items and is divided into 8 domains: In the validation study [34], the CS questionnaire demonstrated excellent internal consistency and test-retest reliability and strong convergent validity with alternative dimensional measures of catatonia, such as the Bush-Francis Catatonia Rating Scale 35 and the Bush-Francis Catatonia Screening Instrument [35].…”
Section: The Catatonia Spectrummentioning
confidence: 99%
“…Most recently, the novel questionnaire for catatonia spectrum has been introduced, which had acceptable agreements with expert ratings. 55 Next, instrumental measures tested gross motor behavior (physiology) using actigraphy and GAITRite. Patients with PS had lower activity levels than controls or patients without PS.…”
Section: Multimodal Assessment Of Psychomotor Slowingmentioning
confidence: 99%
“…Future research might benefit from the development of dedicated self-report instruments. 55 Furthermore, in the current study, we focused on behavioral phenotyping of PS, and did not design the study to assess cognitive slowing. This important feature of PS should be included in future trials using cognitive assessments.…”
Section: Limitationsmentioning
confidence: 99%
“…It consists of 74 items and is divided into 8 domains: Stupor; Mutism; Stereotypes; Mannerisms; Negativism; Automatic obedience; Automatisms and Impulsivity. For each item there is a dichotomous answer “Yes” and “No” [ 28 ].…”
Section: Etiology Components and Scales Of Catatoniamentioning
confidence: 99%